1991
DOI: 10.1103/physrevc.43.2445
|View full text |Cite
|
Sign up to set email alerts
|

Ce129133isotopes in interacting-boson-plus-fermion model

Abstract: The interacting-boson-plus-fermion model is extended to include three fermions. The model is applied to study the odd-mass ' ' Ce isotopes. It is found that the negative-parity states above the band crossings are dominated by (mh»~~) (vh»&2) ' configurations. Energy levels are calculated and compared with experimental data. B (E2) values of the yrast states are calculated and compared with the values calculated by Faessler, Kuyucak, and Wakai. It is found that the calculated B (E2) values reveal sudden drops a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…In [13] it was also shown that the quasi-exact solvability of Eqs. (12) and (13) is not due to the sl(2) Lie-algebra, which is responsible for the quasi-exact solvability of most onedimensional and effectively one-dimensional systems.…”
Section: The Dirac Equationmentioning
confidence: 99%
See 3 more Smart Citations
“…In [13] it was also shown that the quasi-exact solvability of Eqs. (12) and (13) is not due to the sl(2) Lie-algebra, which is responsible for the quasi-exact solvability of most onedimensional and effectively one-dimensional systems.…”
Section: The Dirac Equationmentioning
confidence: 99%
“…(12), and hence is also QES. In [13] it was shown that Eq. (12) and (13) gave the same QES spectrum when…”
Section: The Dirac Equationmentioning
confidence: 99%
See 2 more Smart Citations
“…The parametersb 0 , c 1 are given by, 32) and the coupling constants α i and c 2 (M, N ) are defined by,…”
Section: G Case Vmentioning
confidence: 99%